Stabilization of Rice Bran in Broiler Feed with Natural and Synthetic Antioxidants and Heat Treatment - Gopinger,E (2019)
ABSTRACT The objective of this study was to evaluate different strategies for the oxidative stabilization of rice bran (RB) in the diet of broiler chickens using natural antioxidant additives, synthetic antioxidant additives and heat treatment on performance, breast meat quality and liver fat content and the nutrient digestibility coefficients. Furthermore, the study aimed to evaluate the effects of heat treatment and antioxidants, antioxidant additive treatments, without antioxidants, natural, and synthetic, and to three heat treatments, without heat, dry-heat and moist-heat, after the rice bran was stored for 90 days and then incorporated into the experimental diets. 1080 broilers were arranged in a 3 x 3-factorial randomized design with 10 replicates per treatments. The wet heat treatment of the meal resulted in a higher daily feed intake and body weight at 28 days and better feed conversion than did the meal without heat treatment. No significant interactions were observed between the tested factors on the apparent digestibility of dry matter and ether extract as well as the values of apparent metabolizable energy and apparent metabolizable energy corrected for nitrogen. However, there was significant interaction between the tested factors on the nitrogen retention coefficient; the natural antioxidant and dry heat-treated meal combination presented a lower crude protein digestibility coefficient than those without heat treatment. In conclusion, thermal treatment of this bran proved to be more effective as demonstrated by the performance responses of the birds. Broiler chickens reared up to 28 days of age consuming diets containing 6.5% RB stabilized by heat treatment showed better performance, and the use of antioxidants was not necessary.